Traumatic Diaphragmatic Hernia: An Uncommon Entity - Dangol, Ellina; Yadav, Aditya; Yadav, Umesh Kumar; Rai, Binod Kumar; Pathak, Bipul Vivek (Journal of Society of Surgeons of Nepal, 2022)
Traumatic Diaphragmatic hernia is secondary to penetrating injuries and blunt abdominal and thoracic trauma. It is an uncommon entity. Early diagnosis is necessary to decrease morbidity and mortality. Here we report a case of 22-year-old male with diagnosis of traumatic diaphragmatic hernia. On examination abdomen was distended, guarding present, tender present and bowel sound not appreciated with decreased air entry over left side. CT Scan showed left sided diaphragmatic defect with intrathoracic herniation of abdominal viscera. Laparotomy and exploration revealed a diaphragmatic tear of size 7.5cm X 5cm, with herniation of stomach, spleen, splenic flexure of colon, distal pancreas through diaphragmatic tear.